VISUAL CHARACTER ANALYSIS OF TAKWO TRADITIONAL CLOTHING IN THE ERAU TRADITIONAL CEREMONY OF THE KUTAI KARTANEGARA SULTANATE - Setiawan, Windu; Sugiyamin, Sugiyamin; Cahyono, Nugroho Heri; Triyono, Triyono; Barriyah, Insanul Qisti; Susanto, Moh. Rusnoto (Yayasan Education and Social Center, 2024)
This research aims to 1) Explain clearly and in detail what are the visual characteristics of the Kutai Sultanate Takwo traditional clothes as a characteristic of the Sultanate's clothes; 2) Understand the critical meaning of Kutai Sultanate traditional clothes in the sociocultural context; 3) Knowing the signs (semiotics) in Kutai Sultanate traditional clothes with Pierce's semiotic study in the form of icons, indexes, and symbols. This study uses the Accidental Sampling technique or findings found by chance as a data source. In addition, observation (consisting of pre-observation, direct observation, and non-observation), as well as interviews and documentation, are some of the techniques used in this study. The object of this research is the traditional Clothing of the Kutai Sultanate, namely Takwo. The data analysis technique uses qualitative descriptive analysis. The results showed below: 1) the visual character of Kutai Sultanate traditional clothing has its characteristics from other regional traditional Clothing; 2) the meaning of Kutai Sultanate traditional clothing which illustrates the openness of the Kutai tribe in accepting foreign cultural developments; 3) public awareness in using Kutai Sultanate traditional clothing is getting higher through signs that exist in the accessories component of Takwo cloth